Systemic Rituximab Immunotherapy in the Management of Primary Ocular Adnexal Lymphoma: Single Institution Experience. (August 2015) - Tuncer, Samuray; Tanyıldız, Burak; Basaran, Mert; Buyukbabani, Nesimi; Dogan, Oner
Abstract Purpose: To evaluate the efficacy of systemic rituximab immunotherapy in the management of primary ocular adnexal lymphomas (OAL). Materials and methods: Clinical records of 10 consecutive patients (11 eyes) with biopsy-proven OAL managed with systemic anti-CD20 monoclonal antibody (rituximab; 375 mg/m2 intravenously once every three weeks for 6–8 cycles) between June 2008–March 2013 were evaluated retrospectively. Orbital magnetic resonance imaging and positron emission tomography were performed to evaluate any orbital and systemic involvement, respectively. Clinical response was classified as complete or partial. Results: The age of patients ranged between 27–85 (median, 55) years. Nine patients (90%) presented with unilateral and one (10%) with bilateral conjunctival involvement. Orbit was affected in 4 patients (40%), one of which had also choroidal involvement (10%). None of the patients had systemic involvement at initial presentation. All patients received an average of 7 cycles (range, 6–8) of systemic immunotherapy. After a median follow-up of 31 months (range, 10–61 months), complete response without recurrence could be achieved in 4 eyes (36%) with rituximab monotherapy. No systemic or ocular side effects were observed in any patient. Additional radiotherapy was required in 6 patients (7 eyes; 64%) with partial response or recurrence. Conclusions: Complete regression of primary OALs without recurrence was observed in about one-third of eyes after systemic rituximab monotherapy. Adjunctive radiotherapy was required in remaining two-thirds of the cases to achieve complete response. Thus, considering the balance between high rate of local control and potential ocular complications of radiotherapy, systemic rituximab can be considered as a first-line therapeutic option in the management of primary OAL.